2001
DOI: 10.1023/a:1010698200870
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Structured interviews with 38 Inuit in the community of Holman were conducted to examine Inuit definitions of successful and unsuccessful aging. Qualitative analysis of the interview data suggests that (1) contrary to much of the literature about culture change in the Canadian North, there appear to be no perceivable differences in the ways Inuit of different age cohorts view aging and elderhood; (2) a successful old age is not one necessarily characterized by individual good health, but rather by the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 2 publications
1
29
0
Order By: Relevance
“…Adjustment components focused on the ability to adapt to change in one's life, for example, “keeping up with the changing things around you” 20. Maintenance components focused on continuing previous behaviours, for example, “there is one person I know who is quite old and they're still hunting and everything” 21. Spirituality components focused on the presence of a higher being or connection to a force greater than oneself, for example, “it is important to live with faith and appreciate that we are protected each day” 22.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjustment components focused on the ability to adapt to change in one's life, for example, “keeping up with the changing things around you” 20. Maintenance components focused on continuing previous behaviours, for example, “there is one person I know who is quite old and they're still hunting and everything” 21. Spirituality components focused on the presence of a higher being or connection to a force greater than oneself, for example, “it is important to live with faith and appreciate that we are protected each day” 22.…”
Section: Resultsmentioning
confidence: 99%
“…Very helpful to my neighbors in any way that I can” 14. Social role components focused on one's position or function within a social sphere, for example, “being able to talk to young people, people younger than I who have a long life ahead of them” 21. Quality-of-life components focused on life satisfaction, for example, “leading a simple but happy life” 18.…”
Section: Resultsmentioning
confidence: 99%
“…"Elder" is defined differently in many immigrant and Indigenous communities of the Circumpolar North. Therefore five articles in this analysis (Collings 2000(Collings , 2001Hopkins et al 2007;Torres 2001Torres , 2003 included individuals as young as 35-40 years old because that cutpoint made the most sense in those communities between "young" and "old." Since participants in these studies included individuals over the age of 50 they were included in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Such lay perspectives are not as common in the aging literature as professional definitions that operationalize biomedical health indicators. Little research has addressed the question of healthy aging from an emic (insider's) point of view, one that seeks to understand how the sociocultural environment of a specific community can shape the ways in which people conceptualize what constitutes a good old age (Collings 2001). Cross-cultural research suggests that not all older adults think about healthy aging in the individualistic way that is often defined by Western biomedical practitioners; however, the current literature underrepresents non-Western countries and largely includes culturally homogenous research participants (Cosco et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, aging well is related to active aging (Walker, 2002) and successful aging (Rowe & Kahn, 1987), in which older adults prioritize taking responsibility for their independence, good physical and mental health, and social engagement as they reach the later years of life. In comparison, existing research related to Indigenous older adults and aging well in Canada and the United States has found that aging well means having good friendships (Baskin & Davey, 2015); being involved in and contributing to the community (Baskin & Davey, 2015;Ginn & Kulig, 2015;Lewis, 2014); managing physical health and transmitting wisdom and knowledge (Collings, 2001;Ginn & Kulig, 2015;Lewis, 2011); participating in subsistence activities and caring for others (Hopkins, Kwachka, Lardon & Mohatt, 2007); engaging in spiritual practices (Lewis, 2011); and being in good physical, mental, emotional, and spiritual health (Ginn & Kulig, 2015). In this article, when discussing aging well, we are referring to dominant understandings of aging well that are prevalent in Western (and settler) societies, as these stem from the same neoliberal political environment (Polivka & Longino, 2004) in which decision-makers and service providers work and develop policy and programs in urban communities.…”
Section: A Postcolonial Discourse Analysis Of Community Stakeholders'mentioning
confidence: 95%